2020
DOI: 10.1016/j.ijpharm.2020.119636
|View full text |Cite
|
Sign up to set email alerts
|

Nanosuspensions of a poorly soluble investigational molecule ODM-106: Impact of milling bead diameter and stabilizer concentration

Abstract: Aqueous solubility of a drug substance is an important attribute affecting oral bioavailability.Nanonization, particle size reduction to submicron level, is an elegant approach to improve drug solubility and dissolution by increasing the surface energy, which in turn necessitates the use of stabilizers. The purpose of this study was to develop a nanosuspension of a practically water-insoluble investigational molecule by nanomilling approach using wet media milling. A variety of polymeric and surface active exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…NARNCs were prepared using a planetary ball mill. The grinding time and stabilizer concentrations were critical to determining particle sizes and PDIs [ 14 , 25 ]. Thus, the milling time and the amount of stabilizer were determined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…NARNCs were prepared using a planetary ball mill. The grinding time and stabilizer concentrations were critical to determining particle sizes and PDIs [ 14 , 25 ]. Thus, the milling time and the amount of stabilizer were determined.…”
Section: Resultsmentioning
confidence: 99%
“…In the initial stages of grinding (0 to 125 min), the particle sizes and PDIs decreased rapidly with an increase in milling time because the stabilizers could quickly cover the surface of NAR and facilitate the breakage of crude particles into nanoparticles [14] . However, in the late stages (125 to 175 min), the excess energy due to over-grinding could also disrupt repulsive forces, induce the aggregation of small particles, and affect the physical stability of the system [26] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But the drug-excipient compatibility study showed that there was a high degradation risk between PVP K30 and the related drug. In addition, it is well known that the risk of degradation is higher in liquid formulations such as nanosuspensions and also that a high energy input from grinding media will increase the rate of active ingredient degradation [17]. The optimization study was rebuilt after removing PVP K30 and PVP/VA.…”
Section: Dynamic Viscositymentioning
confidence: 99%